When retrieval cueing fails - Watkins, Michael J.; Tulving, Endel (The British journal of psychology, 1978)
Does presenting a hint, or retrieval cue, for recall of an event change the memory trace for the event even when the cue does not in fact produce recall? An experiment by McLeod, Williams & Broadbent (1971) suggests that it may. A conclusion to this effect would have important theoretical implications. In particular, it would pose difficulties for specifying trace structure. McLeod et al. observed that a retrieval cue was more effective if its target trace had been previously cued, even though this cueing did not elicit recall. Three experiments are described which indicate that this result occurs only if the first, ineffectual cue is presented along with the second cue; if the second cue is presented alone it is less effective than the first. It is concluded that there is currently no evidence that the unsuccessful cueing of an item causes a change in its memory trace.